Global and multicultural public relations - Molleda, Juan-Carlos; Kochhar, Sarabdeep K. 1982- (John Wiley & Sons, Inc., 2019)
"-Significant historical events with economic, political, and social implications have determined the evolution, growth, and sophistication of public relations in countries and regions of the world. -Emergent technologies are dramatically speeding up the development and increasing the reach of organizations, media outlets, citizens, and consumers, which facilitate the exchange of contents from one location to multiple locations instantaneously. -Communication conglomerates, global agencies, and network of independent agencies are major players and influencers in the public relations industry worldwide. -Since the 1940s, European and North American professional associations have made significant contributions to modern and strategic public relations as a profession and to the career development of national and international practitioners. -All types of organizations practice global and multicultural public relations, including government and non-governmental organizations, multilateral organizations, multinational corporations, and agencies. -The complexity of public relations programs increases when organizations operate across borders because of the existence and dynamism of home, host, and transnational stakeholders or publics"--Provided by publisher.